C-Reactive Protein-Based Strategy to Reduce Antibiotic Dosing for the Treatment of Pneumococcal Infection - Ngwa, Donald N.; Singh, Sanjay K.; Agrawal, Alok (Frontiers in Immunology, 2021)
C-reactive protein (CRP) is a component of innate immunity. The concentration of CRP in serum increases in microbial infections including Streptococcus pneumoniae infection. Employing a mouse model of pneumococcal infection, it has been shown that passively administered human wild-type CRP protects mice against infection, provided that CRP is injected into mice within two hours of administering pneumococci. Engineered CRP (E-CRP) molecules have been reported recently; unlike wild-type CRP, passively administered E-CRP protected mice against infection even when E-CRP was injected into mice after twelve hours of administering pneumococci. The current study was aimed at comparing the protective capacity of E-CRP with that of an antibiotic clarithromycin. We established a mouse model of pneumococcal infection in which both E-CRP and clarithromycin, when used alone, provided minimal but equal protection against infection. In this model, the combination of E-CRP and clarithromycin drastically reduced bacteremia and increased survival of mice when compared to the protective effects of either E-CRP or clarithromycin alone. E-CRP was more effective in reducing bacteremia in mice treated with clarithromycin than in untreated mice. Also, there was 90% reduction in antibiotic dosing by including E-CRP in the antibiotic-treatment for maximal protection of infected mice. These findings provide an example of cooperation between the innate immune system and molecules that prevent multiplication of bacteria, and that should be exploited to develop novel combination therapies for infections against multidrug-resistant pneumococci. The reduction in antibiotic dosing by including E-CRP in the combination therapy might also resolve the problem of developing antibiotic resistance.